Удосконалення технології виробництва хлористого вінілу - Курта, Сергій Андрійович (Національний університет "Львівська політехніка", 2015)
Дисертаційна робота присвячена теоретичніому обґрунтуванню та практичному вирішенню науково-технічних проблем, що виявляється у вдосконаленні технології процесів виробництва хлористого вінілу, каталізом прямого та окисного хлоруванням етилену, а також технології процесу термічно ініційованого дегідрохлорування 1,2-дихлоретану з підвищеною селективністю виходу хлористого вінілу зі зменшенням кількості утворення хлорорганічних відходів. На основі встановлення будови реакційних центрів каталізаторів прямого і окисного хлорування етилену та механізму каталізу, дезактивації та регенерації каталізаторів та ініціаторів, з вдосконаленням технологічних схем цих процесів. Розробкою технології нового комплексного методу повної переробки, утилізації хлорорганічних відходів цих виробництв з рециклінгом сировини та матеріалів – вуглеводнів і хлору, було забезпечено більш високий рівень екологічності цих технологій та їх економічної вигідності шляхом переробки хлорорганічних відходів (ХОВ) у товарні продукти: 1,2-дихлоретан, 1,1,2-трихлоретан, вінілхлорид, вініліденхлорид та олігомерні і полімерні продукти. У роботі були запропоновані та вивчені нові вирішення проблем ресурсо- і енергозбереження у промислових технологічних процесах зі зменшенням кількості та повною переробкою хлорорганічних відходів-ХОВ. Особлива увага в роботі приділена комплексній переробці ХОВ в нетоксичні мономери та полімери. Підібрані умови переробки рідких ХОВ шляхом вдосконалення технологічної схеми стадії ректифікації та способом хлорування ненасичених сполук в складі ХОВ. Збільшено кількість продуктового 1,2-ДХЕ на 10–15 %. Проведена також послідовна переробка рідких ХОВ у вінілхлорид та вініліденхлорид шляхом лужного дегідрохлорування 1,2-ДХЕ і 1,1,2-трихлоретану , які входять в склад ХОВ, з конверсією 96%. Диссертация посвящена теоретическому обоснованию и практическому решению научно-технических задач, что проявляется в совершенствовании технологии процессов производства хлористого винила (ВХ), катализом прямого и окислительного хлорированием этилена, а также технологии процесса термического инициированного дегидрохлорирования 1,2-дихлоретана с повышенной селективностью выхода хлористого винила с уменьшением количества образования хлорорганических отходов. На основании установления строения реакционных центров катализаторов и механизма катализа прямого и окислительного хлорирования этилена, дезактивации и регенерации катализаторов, инициаторов по совершенствованию технологических схем этих процессов. Разработкой технологии нового комплексного метода переработкит и утилизации хлорорганических отходов этих производств с рециклингом сырья и материалов – углеводородов и хлора было обеспечено более высокий уровень экологичности этих технологий и их экономической выгодности путем переработки хлорорганических отходов (ХОО) в товарные продукты: 1,2-дихлорэтан, 1,1,2-трихлорэтан, винилхлорид, винилиденхлорид и олигомерные, полимерные продукты. В работе были предложены и изучены новые решения проблем ресурсо- и энергосбережения в промышленных технологических процессах синтеза ВХ с уменьшением количества хлорорганических отходов (ХОО). Особое внимание в работе уделено комплексной переработке ХОО в нетоксичные мономеры и полимеры. Подобранные условия переработки жидких ХОО путем совершенствования технологической схемы стадии ректификации и способом хлорирования ненасыщенных соединений в составе ХОО. Увеличено количество продуктового 1,2-ДХЭ на 10–15%. Проведена также последовательная переработка жидких ХОО до винилхлорида и винилиденхлорида, путем щелочного дегидрохлорирования 1,2-ДХЭ и 1,1,2-трихлорэтана, которые входят в состав ХОО, с конверсией 96%. This dissertation focuses on theoretical development and practical solutions of scientific and technical tasks, which result in the improvement of technological processes of vinyl chloride production through catalysis of direct and oxidative chlorination of ethylene. In addition, it investigates technological processes of thermal initiated dehydrochlorination of 1,2-dichloroethane with increased selectivity of vinyl chloride output with the decreased amount of formed organochlorine wastes (OCW). Determining the structure of reaction centers of catalysts of direct and oxidative chlorination of ethylene and the mechanism of catalysis, deactivation, and regeneration of catalysts and initiators with the enhanced technological schemes of these processes and the development of new technology of an innovative complex method of processing, utilization of OCW from these industries with the recycling of raw materials (hydrocarbons and chlorine) resulted in the enhancement of ecology of these technologies and their economic profitability through processing OCW in commercial products: 1,2-dichloroethane, 1.1.2-trichloroethane, vinyl chloride, vyniledene chloride, as well as oligomeric and polymeric non-toxic products. The structure of active centers of catalysts of direct and oxidative chlorination of ethylene in 1,2-dichloroethane is determined. Furthermore, a new mechanism of complex and crystal-quasi-chemical catalysis of reactions of direct and oxidative chlorination of ethylene with surface complexes of the catalyst, reacting with ethylene, chlorine, hydrogen chloride, and oxygen, is proposed. A new method of preparing the original catalyst of oxidative chlorination of ethylene into 1,2-dichloroethane containing active ingredients – СuСl2·К+, Мg+2 (4–8 %) on the surface of Аl2О3/SіО2 (20–40 % Аl2О3) – is suggested. The implications of the current study include innovative solutions for the problems in resource- and energy-saving in industrial technological processes with the reduction and processing of OCW. Special attention is paid to the complex processing of OCW into non-toxic monomers and polymers. The conditions of processing of liquid OCW by enhancement of the technological scheme of the rectification stage and by chlorination of unsaturated compounds in the composition of OCW are selected. The quantity of product 1,2-dichloroethane is increased in 10–15%. Sequential processing of liquid OCW into vinyl chloride and vyniledene chloride through alkaline dehydrochlorination of 1,1,2-trichloroethane and 1,2-dichloroethane, which are components in OCW with the conversion of 96%, is conducted. A new method of OCW utilization is proposed. It is based on co-polymerization of dehydrochlorinated OCW with the fraction of С5-С9, a by-product of olefins, and polycondensation of OCW into thiokol polymer products with the solutions of sulfide-containing waste in the presence of catalysts of interphase transfer. A possibility of processing up to 75-90% of all OCW from vinyl chloride production with recycling raw materials and intermediate products is illustrated through 5 different methods. The obtained non-toxic thiokol polymers and oligomers have been investigated in terms of their structure and the scope of use. The significant economic and ecological effect from implementation of all enhanced technological processes of industrial production of vinyl chloride is projected.
Усовершенствование технологии производства хлористого винила
Improvement of technological processes of vinyl chloride production
Keywords: 1,2-дихлоретан; вінілхлорид; окислення; хлорування; активність; селективність; каталізатор; етилен; хлороводень; кисень; конверсія; хлорорганічні відходи; вініліденхлорид; трихлоретан; спалювання; ректифікація; дохлорування; утилізація; дегідрохлорування; сополімеризація; рециклінг; фракція; олігомери; поліконденсація; сульфіди; луги; тіоколи; полімери; олігомери; 1,2-дихлорэтан; винилхлорид; окисления; хлорирование; активность; селективность; катализатор; этилен; хлороводород; кислород; конверсия; хлорорганические отходы; винилиденхлорида; трихлорэтан; сжигание; ректификация; дохлорирования; утилизация; дегидрохлорирования; сополимеризация; рециклинг; фракция; олигомеры; поликонденсация; сульфиды; щелочи; тиоколы; полимеры; олигомеры; 1,2-dichloroethane; vinyl chloride; oxidation; chlorination; activity; selectivity; catalyst; ethylene; hydrogen chloride; oxygen; conversion; organochlorine waste (OCW); vyniledene chloride; trichloroethane; burning; rectification; repeated chlorination; utilization; dehydrochlorination; copolymerization; recycling; fraction; oligomers; polycondensation; sulfide; alkali; thiokol; polymers; oligomers